Grain Yield, Nutrient Uptake and Post-harvest Soil Properties of Browntop Millet under Varying Sowing Windows and Nitrogen levels - Saikishore, A.; Rekha, K. Bhanu; Hussain, S. A.; Madhavi, A. (International Journal of Bio-resource and Stress Management, 2021)
A field experiment was conducted during rainy season (June to October, 2019) at College of Agriculture, Rajendranagar, Professor Jayashankar Telangana State Agricultural University, Rajendranagar, Hyderabad, Telangana State, India to find the effect of sowing windows and nitrogen levels on yield, nutrient uptake and post-harvest soil nutrient status of browntop millet. The experiment was laid out in randomized block design with factorial concept and replicated thrice. Treatments consisted of four sowing windows (June 15th, June 30th, July 15th and July 30th) and four nitrogen levels (0, 20, 40 and 60 kg ha-1). Among sowing windows, June 15th recorded higher growth parameters (plant height, leaf area and dry matter production), yield attributes (panicles hill-1, panicle length, weight and grains panicle-1) grain, straw yield, monetary returns and nutrient uptake at harvest (nitrogen, phosphorus and potassium). Post-harvest soil properties (pH, electrical conductivity, organic carbon content, available P and K) were not significantly influenced by sowing windows, but available soil nitrogen was significantly higher with June 15th sowing. Among nitrogen levels, application of 60 kg ha-1 recorded significantly higher growth parameters (plant height, leaf area and dry matter production), yield attributes (panicles hill-1, panicle length, weight and grains panicle-1), grain, straw yield, monetary returns and nutrient uptake at harvest (nitrogen, phosphorus and potassium) but, it was comparable with 40 kg ha-1. Varying nitrogen levels did not significantly influence post-harvest soil properties (pH, electrical conductivity and organic carbon content, available P and K); however, available soil N was significantly higher with the application of 40 kg ha-1.